2017
DOI: 10.1007/s00229-017-0938-3
|View full text |Cite
|
Sign up to set email alerts
|

Lattices in almost abelian Lie groups with locally conformal Kähler or symplectic structures

Abstract: We study the existence of lattices in almost abelian Lie groups that admit left invariant locally conformal Kähler or locally conformal symplectic structures in order to obtain compact solvmanifolds equipped with these geometric structures. In the former case, we show that such lattices exist only in dimension 4, while in the latter case we provide examples of such Lie groups admitting lattices in any even dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 36 publications
0
68
0
3
Order By: Relevance
“…Since G ′ is completely solvable these cohomologies can be computed in terms of the Lie algebra cohomology. Indeed, it follows from [8] (see also [1]) that H * dR (Λ m \G ′ ) ∼ = H * (g ′ ) and H * θ (Λ m \G ′ ) ∼ = H * θ (g ′ ) for any m ∈ N. According to [17], the k th Betti number of g ′ , β k = dim H k (g ′ ), can be computed in terms of the dimension of Z j (g ′ ) = {α ∈ j g * : dα = 0} as follows:…”
Section: Examples Of Solvmanifolds With Lcs Structures Of the Second mentioning
confidence: 99%
See 2 more Smart Citations
“…Since G ′ is completely solvable these cohomologies can be computed in terms of the Lie algebra cohomology. Indeed, it follows from [8] (see also [1]) that H * dR (Λ m \G ′ ) ∼ = H * (g ′ ) and H * θ (Λ m \G ′ ) ∼ = H * θ (g ′ ) for any m ∈ N. According to [17], the k th Betti number of g ′ , β k = dim H k (g ′ ), can be computed in terms of the dimension of Z j (g ′ ) = {α ∈ j g * : dα = 0} as follows:…”
Section: Examples Of Solvmanifolds With Lcs Structures Of the Second mentioning
confidence: 99%
“…A locally conformal symplectic structure (LCS for short) on the manifold M is a non degenerate 2-form ω such that there exists an open cover {U i } and smooth functions f i on U i such that ω i = exp(−f i )ω is a symplectic form on U i . This condition is equivalent to requiring that (1) dω = θ ∧ ω for some closed 1-form θ, called the Lee form. The pair (ω, θ) will be called a LCS structure on M. It is well known that if (ω, θ) is a LCS structure on M, then ω is symplectic if and only if θ = 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6] we considered the existence of invariant LCK structures on solvmanifolds associated to almost abelian Lie groups. Firstly, we showed that there are plenty of almost abelian Lie algebras which admit LCK structures.…”
Section: 2mentioning
confidence: 99%
“…However, almost abelian solvmanifolds equipped with invariant LCK structures are very scarce, since we have shown in [6] that they only occur in dimension 4.…”
Section: 2mentioning
confidence: 99%